Aeration - Advanced Filtration (AAF) Treatment for Reducing Iron and Chloride in Natural Groundwater - Nur Aini Febriyana; Ali Masduqi (IPTEK, LPPM, Institut Teknologi Sepuluh Nopember, 2020)
The production of drinking water for the needs of rural communities generally stilldepend on natural water sources. Communities in rural areas usually use groundwaterfor their daily needs. The water supply in Sampang Regency, East Java Provincehas groundwater problem, i.e. the amount of iron and chloride in the water supplyexceed the maximum amount allowed by PERMENKES No. 492/2010. Therefore,this study proposes a method for drinking water treatment using diffused aeration,as pretreatment, and followed by filtration processing. This pretreatment is meantfor reducing iron. The filtration process is carried out in stages with an advancedfilter of low continuous discharge. The filter media uses resin activated carbon andmicrofiltration to remove suspended and dissolved ions. The results of aeration andfiltration processing (AAF) shows that the preprocessed water have Cl-removal of98.39%, TDS-removal of 97.394%, and iron-removal of 97.41%